Rome, Italy. The Palatine Hill in Rome and its history of research in the 19th century. A report on the latest ›excavations‹ in the archives of Rome. Season 2021 - Sielhorst, Barbara; Santoro, Valentina (e-Forschungsberichte des DAI, 2021)
The Palatine in Rome has a very long and well-documented history of research. However, there is no systematic compilation of the images produced during its exploration. With the help of a research grant (Santoro), extensive materials were collected for its exploration in the 19th century. The images researched in the process are available for inclusion in a geoinformation system on the Palatine (»PalatinGIS«). The GIS serves as a working tool for a study on the visualisation history of the Palatine (Sielhorst). In this article, the role of five images of the Palatine is explained in more detail by briefly describing them and placing them in their context in terms of the history of media and ideas.